Fractionation of a Procyanidin-Rich Grape Seed Extract by a Preparative Integrated Ultrafiltration/Reverse Osmosis/Solid-Phase Extraction Procedure - Esperanza Guerrero-Hurtado; Alba Gutiérrez-Docio; Rebeca Fiedorowicz; Marin Prodanov (Membranes)
The consumption of grape seed extracts is known for its contribution to animal and human health and is associated with its relevant procyanidin content. However, there is a little scientific unanimity whether these properties are due to the procyanidin content or to the length of their polymers. The main reason for this doubt is the technical difficulties related to their separation. Therefore, a preparative separation of grape seed extract was carried out using an integrated ultra/diafiltration procedure with membranes of 300, 30, 5, and 1 kDa molecular mass cut-offs, reverse osmosis and solid-phase extraction to obtain fractions of very high (>300 kDa), high (300–30 kDa), intermediate (30–5 kDa), low molecular mass (5–1 kDa), very-low-mass polar molecules and ions (<1 kDa), and very-low-mass dipole molecules (<1 kDa). Process parameters, mass transfer across the membranes and the quality of separation of each fraction are described and discussed in depth. A high degree of purification was achieved for the higher-molecular-mass fractions (>300, 300–30, and 30–5 kDa), as well as the big majority of procyanidin polymers and oligomers from very-low-molecular-mass species. All fractions were characterized for their procyanidin content by normal phase high-performance liquid chromatography coupled to a photodiode array detector (NP-HPLC-PAD). This analytical technique has shown for the first time that not only do oligomeric procyanidins elute at an increasing order of elution, but polymeric ones also do the same.